2005
DOI: 10.1194/jlr.m400337-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

A phytol-enriched diet induces changes in fatty acid metabolism in mice both via PPARα-dependent and -independent pathways

Abstract: Branched-chain fatty acids (such as phytanic and pristanic acid) are ligands for the nuclear hormone receptor peroxisome proliferator-activated receptor ␣ (PPAR ␣ ) in vitro . To investigate the effects of these physiological compounds in vivo, wild-type and PPAR ␣ -deficient (PPAR ␣ ؊ / ؊ ) mice were fed a phytol-enriched diet. This resulted in increased plasma and liver levels of the phytol metabolites phytanic and pristanic acid. In wild-type mice, plasma fatty acid levels decreased after phytol feeding, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 52 publications
3
48
0
1
Order By: Relevance
“…Other ROS generators, chaetocin and phytol, however, did not show the synergistic antitumor effect, suggesting they differ quantitatively or qualitatively from Luperox in the ROS generation mechanism in T cells (Fig. S4 A-C) (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…Other ROS generators, chaetocin and phytol, however, did not show the synergistic antitumor effect, suggesting they differ quantitatively or qualitatively from Luperox in the ROS generation mechanism in T cells (Fig. S4 A-C) (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…This has been used as a model to study the effects of the accumulation of phytol metabolites on fatty acid metabolism, in particular via the activation of the nuclear hormone receptor peroxisome proliferator-activated receptor a (PPARa), which is an important transcription factor in the regulation of fatty acid metabolism. Both phytanic and pristanic acid have been shown to activate PPARa in vitro (14,15), and more recently, PPARa was also shown to be activated in vivo in mice fed a phytol-enriched diet (13). Figure 1 shows a schematic representation of the metabolism of phytol to phytanic acid and the enzymes involved.…”
mentioning
confidence: 99%
“…Addition of phytol to the diet results in an increase of phytol metabolites in tissues and plasma (6,(11)(12)(13). This has been used as a model to study the effects of the accumulation of phytol metabolites on fatty acid metabolism, in particular via the activation of the nuclear hormone receptor peroxisome proliferator-activated receptor a (PPARa), which is an important transcription factor in the regulation of fatty acid metabolism.…”
mentioning
confidence: 99%
“…The accumulation of phytol has previously been observed in the liver of rats fed with a phytol-enriched diet for 7 d. 23) Phytol is readily converted to phytanic acid in the tissue of such mammals as rats and humans. 24,25) It has been reported that phytol and phytanic acid activated the retinoid X receptor (RXR), 26) sterol carrier protein x (SCP-x), 27) and livertype fatty acid binding protein (L-FABP) in a dosedependent manner.…”
Section: )mentioning
confidence: 99%